Comparison of Heart Rate Variability in Thai Older Adults with Hypertension, Pre-Hypertension, and Normotension - Ruchada Sri-Amad; Nawiya Huipao; Porraporn Sriwannawit; Piyapong Prasertsri; Thapanee Roengrit (The Scientific World Journal)
Objectives. This study aims to compare HRV variables across three cohorts: normotensive (NT), prehypertensive (pre-HT), and hypertensive (HT) and to assess the relationship between the blood pressure (BP) and HRV parameters. Methods. Employing a cross-sectional design, 64 older participants were categorized based on the Joint National Committee’s criteria into NT (n = 10), pre-HT (n = 33), and HT (n = 21) groups. Anthropometric data, lipid profiles, and HRV indices were evaluated. HRV data were obtained from the Polar V800 chest strap device using HRV Kubios software for data analysis of short-term recordings lasting 10 minutes. This analysis encompasses both time and frequency domain assessments. The time domain includes the standard deviation of NN intervals (SDNN), the root mean square of successive RR interval differences (RMSSD), and the percentage of successive RR intervals differing by over 50 ms (pNN50). The frequency domain includes low frequency (LF), high frequency (HF), and the ratio of LF-to-HF power (LF/HF). Data were statistically analyzed via one-way analysis of variance (ANOVA) and Pearson correlation. Results. The HT group exhibited significantly lower values in SDNN, pNN50, LF power, and HF power in comparison to the NT group (P<0.05). Moreover, the HT group had a significantly lower SDNN value compared to the pre-HT group (P<0.05). Inverse associations were uncovered between systolic and diastolic blood pressure and SDNN, pNN50, and HF power (P<0.05). Multiple regression further highlighted the significance of systolic and pulse pressure concerning HF power (P<0.05). Conclusions. HRV indices are reduced in Thai older adults with HT compared with those with NT. Monitoring HRV in older adults can provide valuable insights into autonomic function and cardiovascular disease risk.